Proliferation and osteoblast differentiation mice dental pulp stem cells between enzyme digestion and outgrowth method - Farinawati Yazid,; Nur Atmaliya Luchman,; Rohaya Megat Abdul Wahab,; Shahrul Hisham Zainal Ariffin,; Sahidan Senafi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The isolation method for dental pulp stem cells (DPSCs) is still unclear to obtain a conducive environment for DPSCs to proliferate. Enzymatic digestion and outgrowth method are two commonly used methods for DPSCs isolation but are not well characterized in mice DPSCs. This study aimed to compare these isolation methods and differentiation potential of mice DPSCs into bone cells. Dental pulp was extracted from mice’s incisors and subjected to isolation either by collagenase 1A or culture of pulp tissue in complete alpha-Modified Eagle Medium (αMEM). Both cells isolated were cultured until passage 4 and subjected to in vitro proliferation and differentiation analysis. Both cells exhibited fibroblastliked morphology, but cells isolated by enzyme digestion proliferate faster compare to outgrowth method. After 21 days of osteoblast differentiation, DPSCs isolated from enzyme digestion method showed alkaline phosphatase (ALP) activity slightly different as compared to outgrowth method. In conclusion, there is a significant difference between the cells isolated from enzyme digestion compare to outgrowth method with regard to proliferation and osteoblast differentiation. Thus, it is preferable to isolate by enzyme digestion as it is faster and consistent compared to outgrowth method.